Falsely elevated plasma metanephrine in patients taking midodrine. (July 2018) - Emms, Holly; Farah, George; Shine, Brian; Boot, Chris; Toole, Barry; McFadden, Martin; Lam, Leo; Ou, Zong-Quan; Woollard, Gerald; Madhavaram, Hima; Kyle, Campbell; Grossman, Ashley B
Plasma metanephrines have become the biochemical test of choice for suspected phaeochromocytomas and paragangliomas in many institutions. We encountered two separate cases of significantly elevated plasma metanephrines in patients taking midodrine, a sympathomimetic drug used in the treatment of severe postural hypotension, in the absence of a diagnosis of phaeochromocytomas and paragangliomas. Upon stopping midodrine treatment, plasma metanephrine concentrations returned to normal in both patients. To explore the hypothesis that midodrine or its metabolite desglymidodrine might interfere with the metanephrines assay, we tested the interaction of midodrine with metanephrine assays from two different centres. High-performance liquid chromatography tandem mass spectrometry on plasma samples and on methanolic extract of midodrine demonstrated co-elution of the metabolite desglymidodrine with metanephrine. We conclude that patients taking midodrine may have falsely elevated plasma metanephrine as a result of analytical interference, and clinicians need to be aware of this problem.